Critical analysis of the drug promotional literatures advertised in a tertiary care hospital - Dhodi, D. K.; Chavan, M. S.; Dawer, F.; Desai, S. A.; Bhoir, A. R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of the study was to critically analyse the drug promotional literatures (DPLs) advertised in a tertiary care hospital. Methods: This observational study was conducted in department of pharmacology, grant government medical college. The data was collected over a period of 3 months after obtaining permission from Institutional Ethics Committee. Around 200 DPLs were collected from different specialty OPDs. Promotional literatures in the form of medical equipment’s, ayurvedic medicine, drug monography, reminder advertisement, identical advertisement and drug name list were excluded from the study. Data compiled was compiled in an excel sheet. The complied data were analyzed with the help of tables and graphs. Results: In our study, the name of the active ingredient, their brand name and the therapeutic uses were mentioned in all the DPLs (100%). The dosage form of the drug was addressed in 85%, whereas the schedule was present in 58% of the DPLs. Most of the DPLs had mentioned about the positive effects of the drug, while few of them described the negative effects of the drugs, namely, adverse drug reactions (39%), precautions to be taken (36%), contraindications (36%) and various drug interactions (33%). Conclusions: A diverse set of results were obtained when a cohort of 200 promotional literatures were analyzed wherein the advantageous effects were highlighted covering the detrimental effects of the drug. DPLs were not in line and accordance with WHO guidelines, but where modified according to the company preferences.